A circularly polarized meander loop antenna for unmanned aerial vehicle satellite navigation system. Issue 5 (1st February 2022) - Han, Tuan‐Yung; Sim, Chow‐Yen‐Desmond; Chen, Chin‐Yang
Abstract: A circularly polarized (CP) meander loop antenna used in the unmanned aerial vehicle (UAV) satellite navigation system is proposed. The planer size of the proposed antenna is 45.6 × 38.4 mm 2 and it was printed on a thin flexible substrate with a thickness of only 0.063 mm. Thus, it has the advantages of a lightweight, low profile, and ease in manufacturing. The proposed antenna design utilizes a loop antenna and has applied a perturbed element into the loop to excite two equal amplitude electric fields with a 90° phase difference, thereby exciting a good CP radiation. The measured 10‐dB impedance bandwidth of the proposed antenna was 9.3% (1.48–1.624 GHz), and its corresponding 3‐dB axial ratio (AR) bandwidth was 2.3% (1.555–1.591 GHz). The CP operating band of the proposed antenna can cover the GPS L1, Galileo E1, and Beidou B1 band (1.559–1.591 GHz).